An on-board energy and environmental analysis within the COVID-19 effects - UYAR, TANAY SIDKI (My University, 2023)
The marine transportation industry, which has made significant steps in recent years to combat climate change and global warming, is heavily influenced by regional and worldwide economic trends. The COVID-19 pandemic, which began in China at the end of 2019 and spread to the rest of the world in the first quarter of 2020, caused the global economy and marine transport to decline by 4.1% in 2020. It is proposed in this study to investigate various scenarios by modelling this circumstance that has unexpectedly occurred using decision assistance technologies.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Atmosfer Bilimleri ve Meteoroloji Mühendisliği; Jeofizik Mühendisliği; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Atmospheric Sciences and Meteorological Engineering; Geophysical Engineering; Engineering and Technology; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Yerbilimleri; Sosyal Bilimler Genel; JEOKİMYA VE JEOFİZİK; METEOROLOJİ VE ATMOSFER BİLİMLERİ; ÇEVRE ÇALIŞMALARI; Natural Sciences (SCI); Social Sciences (SOC); GEOSCIENCES; SOCIAL SCIENCES, GENERAL; GEOCHEMISTRY & GEOPHYSICS; METEOROLOGY & ATMOSPHERIC SCIENCES; ENVIRONMENTAL STUDIES; Küresel ve Gezegensel Değişim; Fizik Bilimleri; Atmosfer Bilimi; Yönetim, İzleme, Politika ve Hukuk; Global and Planetary Change; Physical Sciences; Atmospheric Science; Management, Monitoring, Policy and Law; energy analysis; energy modelling; greenhouse gas emissions; leap; reference energy system; RES; reference energy system; RES; energy analysis; energy modelling; leap; greenhouse gas emissions ACCESS OPTIONS